Kompilasi ucaptama tahunan rektor (Kolej Universiti Kejuruteraan Utara Malaysia, 2006)
On higher education in Malaysia; collection of speeches of the rector of Kolej Universiti Kejuruteraan Utara Malaysia for the years 2003-2006